Investigating The Linear and Nonlinear Relationship Between Public Expenditure and Economic Growth in Turkey - Demir, Ömer; Uzan, Serhat (Şırnak Üniversitesi, 2022)
This study examines the linear and nonlinear relationship between public expenditure and economic growth in Turkey for the period 1960-2020, in the context of short-run and long-run dynamics. For this purpose, the study uses ARDL & NARDL approach to determine whether the changes in the rates of public expenditure affect the GDP per capita growth rate in a linear and non-linear context in the short- run and long-run, and if these effects exhibit an asymmetric character in the expansion and contraction periods of the Turkish economy. The findings show that both a linear and non-linear long run relationship is defined between the public expenditures rate and the GDP per capita growth rate. Accordingly, a long-run linear relationship is determined between public expenditure and the GDP per capita growth rate, but the coefficients are not statistically significant. According to another finding, a long-run nonlinear relationship is defined between public expenditure and the GDP per capita growth rate, and it is determined that negative shocks in public expenditure negatively affect the GDP per capita growth rate. In addition, Wald test result shows that public expenditure affect growth rate asymmetrically in the long run.

Bu çalışma, 1960-2020 dönemi için Türkiye’de kamu harcamaları ve ekonomik büyüme arasındaki doğrusal ve doğrusal olmayan ilişkiyi kısa ve uzun dönem dinamikleri bağlamında sınamaktadır. Bu amaçla çalışma, kamu harcamaları oranındaki değişmelerin kişi başına GSYH büyüme oranını kısa ve uzun dönemde doğrusal ve doğrusal olmayan bir şekilde etkileyip etkilemediğini ve varsa bu etkilerin Türkiye ekonomisinin genişleme ve daralma dönemlerinde asimetrik bir karakter sergileyip sergilemediğini tespit etmek için ARDL & NARDL yaklaşımını kullanmaktadır. Elde edilen bulgular, kamu harcamaları oranı ve kişi başına GSYH büyüme oranı arasında hem doğrusal hem de doğrusal olmayan uzun dönemli bir ilişkinin tanımlandığını göstermektedir. Buna göre, kamu harcamaları ve büyüme arasında uzun dönemli doğrusal bir ilişki belirlenmiştir, ancak katsayıların istatistiksel olarak anlamlı olmadığı bulunmuştur. Bir diğer bulguya göre, kamu harcamaları ve büyüme arasında uzun dönemli doğrusal olmayan bir ilişki tanımlanmıştır ve kamu harcamalarındaki negatif şokların kişi başına GSYH büyüme oranını uzun dönemde negatif olarak etkilediği tespit edilmiştir. Ayrıca Wald testi sonucu, Türkiye' de kamu harcamalarının uzun dönemde büyüme oranını asimetrik olarak etkilediğini göstermektedir.
TÜRKİYE’DE KAMU HARCAMALARI VE EKONOMİK BÜYÜME ARASINDAKİ DOĞRUSAL VE DOĞRUSAL OLMAYAN İLİŞKİNİN İNCELENMESİ